Implementasi Teknologi Hibrid Film Tebal Pada Rangkaian Filter High Pass Butterworth Orde Dua - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Hybrid system is one of the alternatives of miniaturizing an electronic circuit. The hybrid system is built using thick film hybrid or thin film hybrid on substrata or by multi-chip hybrid. Passive components and the interconnection pattern (conductors) of the eletronic circuit is implemented by thick or thin-film technology on substrate. The objective of this research is implementing thick film technology for highpass second order Butterworth filter circuit. The result of testing of the design specification was measured from the the frequency response, cut-off frequency and slew-rate of the filter circuit using PSPICE program. Thick film hybrid technology used screen printing as a method to build integrated circuits. The method consisted of several simple repeatable basic steps, they were screen making, printing, and burning. As well as those three basic steps there were also cleaning process, soldering, characteristic testing, and packaging. Screen printing was similar to printing process in general, it needed a screen, substrata, paste and squeege. Using a squeege which was coated with chemical resist, paste is squeezed through a screen which was close-fitted on a substrate. With a circuits layout pattern laid on the screen, this process produced the layout of the circuit on the substrat. The result of measurement and analisist showed mean errors of 14,4% for R1, 20,42% for R2, -11,6% for C1, -16.33% for C2, the filter with 934,5 Hz cut-off frequency, and 28,27 dB slew rate. The result also showed the stability of the frequency response for different voltage and frequency.